2017
DOI: 10.1103/physrevb.95.104109
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hookean statistical mechanics of clamped graphene ribbons

Abstract: Thermally fluctuating sheets and ribbons provide an intriguing forum in which to investigate strong violations of Hooke's Law: large distance elastic parameters are in fact not constant, but instead depend on the macroscopic dimensions. Inspired by recent experiments on free-standing graphene cantilevers, we combine the statistical mechanics of thin elastic plates and large-scale numerical simulations to investigate the thermal renormalization of the bending rigidity of graphene ribbons clamped at one end. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…In Ref. [44], it was shown that this simplified dual model gives results consistent with graphene simulations [45] that incorporate explicitly the energetics of carbon-carbon bonds. As for anharmonic contributions to the free energy we emphasize that our model incorporates nonlinearities through the nonlinear strain tensor u ij , which leads to a critical nonlinear stretching term once in-plane phonons are integrated out.…”
Section: Simulation Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…In Ref. [44], it was shown that this simplified dual model gives results consistent with graphene simulations [45] that incorporate explicitly the energetics of carbon-carbon bonds. As for anharmonic contributions to the free energy we emphasize that our model incorporates nonlinearities through the nonlinear strain tensor u ij , which leads to a critical nonlinear stretching term once in-plane phonons are integrated out.…”
Section: Simulation Methodsmentioning
confidence: 73%
“…[25] and the non-Hookean statistical mechanics of thermalized ribbons clamped at one end only, with the associated scale-dependent stiffening of the bending rigidity, studied in Ref. [44].…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
“…Following refs. 25 , 32 , we will use . This corresponds to a Young’s modulus about an order of magnitude lower than for real graphene 33 , 34 , in order to facilitate equilibration in our computer simulations.…”
Section: Resultsmentioning
confidence: 99%
“…However, physically, the maximum value of the γ FvK number is γ FvK ≈ 10 14 . This value does not occur for shells since it describes the behavior of a 200 µm square sheet of graphene [48]. Graphene is one-atom thick membrane with high in plane Young's modulus (Y = 500 GPa).…”
Section: Quantification Of Bending Versus Stretching Deformationmentioning
confidence: 99%